2018
DOI: 10.1371/journal.pbio.2005821
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide functional analyses of plant coiled–coil NLR-type pathogen receptors reveal essential roles of their N-terminal domain in oligomerization, networking, and immunity

Abstract: The ability to induce a defense response after pathogen attack is a critical feature of the immune system of any organism. Nucleotide-binding leucine-rich repeat receptors (NLRs) are key players in this process and perceive the occurrence of nonself-activities or foreign molecules. In plants, coevolution with a variety of pests and pathogens has resulted in repertoires of several hundred diverse NLRs in single individuals and many more in populations as a whole. However, the mechanism by which defense signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 98 publications
1
72
0
2
Order By: Relevance
“…In plants, NLRs also oligomerize through their N-terminal domains, notably the common and widespread CC domain (Bentham et al, 2018). The CC domain of some, but not all NLRs, triggers cell death when expressed as a truncated domain indicating that it can undertake oligomerization on its own (Maekawa et al, 2011;Casey et al, 2016;Cesari et al, 2016;Wróblewski et al, 2018). However, the molecular mechanisms that underpin CC-NLR activation and subsequent execution of HR cell death have remained largely unknown until very recently.…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, NLRs also oligomerize through their N-terminal domains, notably the common and widespread CC domain (Bentham et al, 2018). The CC domain of some, but not all NLRs, triggers cell death when expressed as a truncated domain indicating that it can undertake oligomerization on its own (Maekawa et al, 2011;Casey et al, 2016;Cesari et al, 2016;Wróblewski et al, 2018). However, the molecular mechanisms that underpin CC-NLR activation and subsequent execution of HR cell death have remained largely unknown until very recently.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…The N-terminal CC domain of a subset of CC-NLR proteins can mediate self-association and trigger HR cell death when expressed on its own (Bentham et al, 2018). However, to date truncation experiments have been conducted based on educated guesses of domain boundaries (Maekawa et al, 2011;Casey et al, 2016;Cesari et al, 2016;Wróblewski et al, 2018). Moreover, one amino acid difference in the length of the assayed truncation can affect cell death inducing activity (Casey et al, 2016).…”
Section: Mu Mutagenesis Of Nrc4 Reveals a Short 29 Amino Acid N-termimentioning
confidence: 99%
“…6). In addition, a recent study reported 346 that 13 of 22 Arabidopsis CNLs in group B that belong to G10 in our classification trigger 347 cell death in Arabidopsis (49). Taken together, these results indicate that many G10-CCs in 348 Solanaceae and Brassicaceae plants have the potential to trigger cell death (SI Appendix, 349 Table S3).…”
mentioning
confidence: 52%
“…In addition, a recent study 307 reported that significantly high portion of the predicted CC domain of the CNLs in A. 308 thaliana ecotype Columbia-0 triggered cell death (49). All of the CNLs from group B ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation